ACCULTURATION OF CULTURE AND RELIGION IN THE GREBEG SEWULAN TRADITION IN DAGANGAN DISTRICT, MADIUN REGENCY - SAHAL MASQAN ASY’ARIE; ANDHITA RISKO FARISTIANA (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This research aims to get to know and examine in more depth the background of the Grebeg Sewulan tradition in Sewulan Village, Dagangan District, Madiun Regency, East Java. This research also explains the origins of the tradition, the implementation process, and the acculturation values ​​contained in the tradition. This research method uses qualitative research methods with an ethnographic approach and uses acculturation theory. Data collection techniques: observation, interviews and documentation. The focus of this research is to examine the acculturation of the Grebeg Sewulan tradition. The results of the research found that the Grebeg Sewulan tradition is an activity held once a year in the month of Muharram between Tuesday Kliwon and Friday Legi to worship heirlooms. The result of acculturation from this sewulan grebeg is the creation of heritage from Hindu, Buddhist and Islamic cultures. This acculturation can be seen in the values ​​contained during the penjamasan procession, namely that people hope to return to purity in the Islamic New Year. This is symbolized by wearing heirlooms, which means that all living things will return to their creator, just like heirlooms return to their container.